Análisis sobre la Protección de los Derechos Reproductivos de las mujeres trabajadoras y el Derecho a la Igualdad Material en virtud de su estado de embarazo - Guarnizo Samaniego, Stalin Andrés (2023)
The present degree work is entitled: “Analysis on the protection of the reproductive rights of working women and the right to material equality by virtue of their state of pregnancy”, and its interest in developing is due to the fact women throughout history it has always been part of a group of fragility and violation of rights in different areas, whether social, family work, the latter being the point of emphasis of this legal study with respect to pregnant women. The carried out study shows that both public and private companies that have pregnant women amondeg their workers violate their reproductive rights and the rights to material equality by virtue of their state of pregnancy because employers, due to unfounded decisions , dissociate them from their jobs positions or they are assigned a different position from the one developed by pregnant women, which brings with them a number of affectations such as in the economic field because they are detached form their economic remuneration that they received monthly, another present factor is the emotional one because women in this state are more vulnerable to situations that denote the pretense of strong mood changes, which would affect their situation of emotional stability, and the development of psychological disorders. In this degree work it was possible to apply materials and methods that allowed the development of the investigation, in the same way a file study was carried out based on surveys and interviews applied to legal professionals, whose results served to demonstrate that there is a violation of the reproductive rights of workers and the right to material equality by virtue of their state pregnancy, for which a legal proposal is proposed that will guarantee the right to job stability, of pregnant women in order to protect the rights inherent to motherhood. Keywords: reproductive rights, material equality, pregnant women, working people.